Association of Breakfast Routine with Quality Of Life and Sleep Quality in University Students; A Cross Sectional Survey - Maham Khalid, Ahmed Jamal, Amna Iram, Tamknat Ilyas, Muhammad Adil, Bilal Umar, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: The relationship between certain breakfast consumption habits and mental health has been reported previously, many observational studies showed association between breakfast routine and academic performance. However, few studies regarding sleep quality with breakfast consumption have been carried out. Objective: To determine the association of breakfast routine with quality of life and sleep quality in university students. Methods: This was a cross sectional survey conducted among 490 students of Doctor of Physical Therapy, using the sample of convenience. The included students were both male and female, aged 20-27 years old and studying in their 3rd or above professional year. The students with a diagnosed psychological disorder and on a diet plan for weight reduction were excluded. The questionnaire was comprised of demographics such as age, body mass index, academic year, gender, self -perceived quality of sleep, grade in academic assessment, dietary habits and breakfast consumption frequency. Results: The main results showed that 68.6% students between 20-23 years and rest of 31.4% were between 24-27 years of age and gender majority were female 77.3%. According to self-perceived sleep, there were 82.7% having good sleep quality and 17.3% having poor sleep quality. The findings regarding consumption showed that majority 50.4% were taking breakfast 5-7 days a week, 27.6% occasionally 3-4 days/week and 22% rarely. Chi Square test showed that either food consumption routine or type were not associated with academic performance (p value 0.264, 0.188 respectively) or sleep quality (p value 0.997, 0.959 respectively). Conclusions: Breakfast habits are not significantly associated with academic grades. Also, there is no significant association found between breakfast habits and sleep quality.